Evaluation of prescribing pattern of the private practitioners by the undergraduate medical students - Rahman, Zaida; Nazneen, Rumana; Begum, Mahmuda (Bangladesh Journal of Pharmacology, 2008)
To sensitize the fourth year undergraduate medical students about rational prescribing, 600 prescriptions of private practitioners were collected by them and analyzed using WHO/INRUD indicators. There were average 3.81 drugs per prescriptions. Drugs were prescribed in generic name only in 5 prescriptions. About 50% drugs were prescribed from the Essential Drug List; only 17.5% of prescriptions were complete in respect to patient medical information. Antibiotics were prescribed in 72.5% of the prescriptions; injections were prescribed in about 12.1% of the prescriptions. Although the exercise revealed few elementary aspects of the prescribing, the medical students participated in the exercise enthusiastically and perhaps understood the issues related to rational prescribing effectively.